Théodore de Banville : artiste ou artisan ? - Malinowski, Wiesław Mateusz (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2019)
This paper puts forward a reflection upon the status of Theodore de Banville in the literary Pantheon by making an attempt to determine the proportions of art and artisanry in his poetic work. While Banville deserves to be referred to as an artist, providing the term is based on the 19th century definition, the name of an artisan, so often used with reference to his person by critics and literary historians might also be justified. Looking at Banville’s work more closely, analyzing the role of his creative inspiration and patiently built text structure, observing the importance attached by the author to the versification techniques, his love for technical difficulty, his meticulousness and his writing skills, but also the frequency with which he creates images and metaphors referring to what was previously called ‘mechanical arts’, long story short, taking into account everything that falls under the category of poetic techniques, the answer to the question posed in the title of the paper, whether Banville was an artist or an artisan, is that he was both.